Evaluate slip torque of an interference fit using preloaded, non-linear large strain simulation in MSC MARC. (2023) - Karale, Ajinkya; MohanKumar, V.; Rane, Sandeep
Abstract: Automotive component assemblies have single or multiple non-linearities. These are either geometric, material or contact related non linearities. In the product assembly discussed in this paper, we came across preloaded, non-linear large strain i.e., to evaluate the slip torque of an interference fit. Generally, linear simulations are performed with all the three linear considerations, but in this problem statement there was compressive preload due to interference fit, which is carried further in the torque slip evaluation of the assembly. The material at the interference area is prone to fracture/crushing i.e., large strains, complete element destruction and new adaptive mesh formation therefore must be considered. So, to consider the Pre-Load as well as non-linear large strain conditions, CAE simulations were performed in MSC Marc Non-linear Solver. This paper would talk about in-depth results interpretation of Preloaded (Compression due to interference fit) and nonlinear large strain simulations to evaluate the rotational moment at which shaft begins to slip losing its interference fit. In Non-Linear simulation we were able to capture this dynamic interaction between the required portion of rotor and shaft and demonstrate the same with good accuracy. This activity of Pre-Loaded, Non-linear Large strain simulation helped us understand how mechanical system behavior is changing with respect to its mathematics or we can say accurate numerical interpretation.